Monster - Myers, Walter Dean 1937-2014; Myers, Christopher (New York HarperTempest/Amistad, 2004)
While on trial as an accomplice to a murder, sixteen-year-old Steve Harmon records his experiences in prison and in the courtroom in the form of a film script as he tries to come to terms with the course his life has taken
Michael L. Printz Award, 2000; Coretta Scott King Award honor book; National Book Award finalist
1
Keywords: African Americans -- Fiction; Prisons -- Fiction; Self-perception -- Fiction; Trials (Murder) -- Fiction